Prediction of solar radiation with air temperature data in a coastal location in Tamilnadu - MUGRAPAN, A.; SIVAPRAKASAN, SUBBARAYAN; MOHAN, S. (MAUSAM, 2011)
The objective of this study is to evaluate the performance of the Hargreaves’ Radiation formula in estimating daily solar radiation for an Indian coastal location namely Annamalainagar in Tamilnadu State. Daily solar radiation by Hargreaves’ Radiation formula was computed using the observed data of maximum temperature, Tmax and minimum temperature, Tmin, sourced from the India Meteorological Observatory located at Annamalainagar and employing the adjustment coefficient KRS of 0.19. Daily solar radiation was also computed using Angstrom-Prescott formula with the measured daily sunshine hour data. The differences between the daily solar radiation values computed using the formulae were more pronounced in year around. Hence, the adjustment coefficient KRS is calibrated for the study location under consideration so that the calibrated KRS could be used to better predict daily solar radiation and hence better estimation of reference evapotranspiration.